Internal Social Capital and the Attraction of Early Contributions in Crowdfunding. (January 2015) - Colombo, Massimo G.; Franzoni, Chiara; Rossi–Lamastra, Cristina
The nascent crowdfunding literature has highlighted the existence of a self–reinforcing pattern whereby contributions received in the early days of a campaign accelerate its success. After discussing what sustains this pattern, we maintain that the internal social capital that proponents may develop inside the crowdfunding community provides crucial assistance in igniting a self–reinforcing mechanism. Results of an econometric analysis of a sample of 669 Kickstarter projects are consistent with this view. Moreover, the effect of internal social capital on the success of a campaign is fully mediated by the capital and backers collected in the campaign's early days.